2020
DOI: 10.1016/j.jaci.2019.12.911
|View full text |Cite
|
Sign up to set email alerts
|

Nasal DNA methylation profiling of asthma and rhinitis

Abstract: Background: Epigenetic signatures in the nasal epithelium, which is a primary interface with the environment and an accessible proxy for the bronchial epithelium, might provide insights into mechanisms of allergic disease. Objective: We aimed to identify and interpret methylation signatures in nasal epithelial brushes associated with rhinitis and asthma. Methods: Nasal epithelial brushes were obtained from 455 children at the 16-year follow-up of the Dutch Prevention and Incidence of Asthma and Mite Allergy bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 46 publications
4
68
0
Order By: Relevance
“…Other genes relevant to epithelial barrier function ( CDH26 , CDHR3 ) were also found differentially methylated 95,97 . In addition to CDHR3, another genes selectively expressed in ciliated epithelial cells, ZMYND10 91 was found to be differentially methylated, which is consistent with an altered airway epithelial composition in asthma. Only one study to date analysed CpG methylation in bronchial biopsies from asthma patients and healthy controls, but this analysis was focussed on methylation patterns associated with remission of asthma 99 …”
Section: Epigenetic Factors and The Epithelial Barrier In Asthmamentioning
confidence: 99%
“…Other genes relevant to epithelial barrier function ( CDH26 , CDHR3 ) were also found differentially methylated 95,97 . In addition to CDHR3, another genes selectively expressed in ciliated epithelial cells, ZMYND10 91 was found to be differentially methylated, which is consistent with an altered airway epithelial composition in asthma. Only one study to date analysed CpG methylation in bronchial biopsies from asthma patients and healthy controls, but this analysis was focussed on methylation patterns associated with remission of asthma 99 …”
Section: Epigenetic Factors and The Epithelial Barrier In Asthmamentioning
confidence: 99%
“…7 The possible protective effect of pet ownership might be explained by an immunomodulatory effect of exposure to allergens, endotoxins, or bacteria 7 or by affecting DNA methylation. 25 However, the F I G U R E 2 A, Association between demographic risk factors and any atopic disease and recurrent respiratory tract infections. CI, confidence interval; GA, gestational age; mat, maternal; OR, odds ratio; pat, paternal; RRTI, recurrent respiratory tract infections.…”
Section: Child's Comorbiditymentioning
confidence: 99%
“…With respect to study design, further studies in longitudinal cohorts are required to develop predictive nasal methylation panels suitable for early prediction of asthma, as well as gene candidate studies to analyze genes found to be significantly related with asthma. Since sensitization to aeroallergens has been found to drive an overlap between nasal methylome correlated with asthma and rhinitis (35), future studies should carefully consider the coexistence of rhinitis when investigating the association of DNA methylation with asthma in nasal epithelium. Furthermore, it would be fascinating to study the influence of aging on DNA methylation on this tissue, which is particularly exposed to environmental factors.…”
Section: Future Perspectivesmentioning
confidence: 99%